Intellectual property and sustainable markets - Rognstad, Ole-Andreas; Ørstavik, Inger B. (Elgar intellectual property and global development series, 2021)
"Discussing how intellectual property (IP) rights play a role in tackling the challenge of securing sustainable development, renowned scholars consider how the core objective of IP rights to promote innovation and development of new knowledge aligns with the UN Sustainable Development Goals (SDGs). This authoritative book provides an in-depth analysis of the multi-faceted interface between this core objective and the SDGs. Chapters analyse selected interrelations between IP law and other areas of law, including energy and financial law. Contributors explore the dimension of social development through timely examples such as the global solar photovoltaic market, the trend towards reusing and recycling, and the digital distribution of news services. This thought-provoking book argues for sustainable markets as an overreaching and contextual approach to the role of IP rights in tackling the challenges of the UN SDGs. Taking a market-based approach to IP rights and the SDGs, this engaging book will be of value to students and scholars of intellectual property and environmental law, as well as policy makers, practitioners and NGOs concerned with corporate social and environmental responsibility"--